The Immunological Basis of Liver Allograft Rejection - Ronca, Vincenzo; Wootton, Grace; Milani, Chiara; Cain, Owen (Frontiers in Immunology, 2020)
Liver allograft rejection remains a significant cause of morbidity and graft failure in liver transplant recipients. Rejection is caused by the recognition of non-self donor alloantigens by recipient T-cells. Antigen recognition results in proliferation and activation of T-cells in lymphoid tissue before migration to the allograft. Activated T-cells have a variety of effector mechanisms including direct T-cell mediated damage to bile ducts, endothelium and hepatocytes and indirect effects through cytokine production and recruitment of tissue-destructive inflammatory cells. These effects explain the histological appearances of typical acute T-cell mediated rejection. In addition, donor specific antibodies, most typically against HLA antigens, may give rise to antibody-mediated rejection causing damage to the allograft primarily through endothelial injury. However, as an immune-privileged site there are several mechanisms in the liver capable of overcoming rejection and promoting tolerance to the graft, particularly in the context of recruitment of regulatory T-cells and promotors of an immunosuppressive environment. Indeed, around 20% of transplant recipients can be successfully weaned from immunosuppression. Hence, the host immunological response to the liver allograft is best regarded as a balance between rejection-promoting and tolerance-promoting factors. Understanding this balance provides insight into potential mechanisms for novel anti-rejection therapies.